B. P. Mansurov’s Trip to East in 1856—1857 - Yu. E. Kondakov; D. S. Fedotiev (Научный диалог)
The article deals with the activities of the official of the Maritime Ministry B. P. Mansurov, sent in 1856 by Grand Duke Konstantin Nikolayevich to the Turkish East in order to compile a guide for pilgrims and collect information about their situation in Palestine. The relevance of the study is due to the fact that Mansurov's activities marked the beginning of the construction of infrastructure for Russian pilgrims, called ‘Russian Palestine’. The material for the study are three reports by Mansurov. It is shown that the first report was dictated by the rivalry between the Grand Duke Konstantin Nikolayevich and the head of the Ministry of Foreign Affairs A. M. Gorchakov. Attention is paid to the second version of the report, handed over to the emperor and ministers, in which criticism of the Foreign Ministry was smoothed over. Particular attention is paid to the fact that, under the influence of Gorchakov, Mansurov tried to remove the most acute political problems from the third version of the report, which was already sent to senior officials. It is proved that Mansurov’s report received a wide response and became the subject of consideration by the Committee of Ministers. The issue of the further fate of Mansurov’s report, published in the form of a book entitled “Orthodox worshipers in Palestine”, which was supposed to draw attention to the problem of pilgrims and raise funds to help them, is considered.